Obtaining help by standing higher: The mediating role of moral reputation - Ming, Xiaodong; Fu, Jingyu; Yang, Jianfeng (Frontiers in Psychology, 2022)
Drawing on the social cognitive chain of being (SCCB) theory and heuristic perspective, the present study explored whether and how social targets’ vertical spatial position influences the help the social targets can get from others. Study 1 demonstrated that individuals would be more likely to help social targets who were presented on a higher vertical spatial position than those who were presented on a lower vertical spatial position. In Study 2, an experimental-causal-chain design was adopted for further testing the mediating role of moral reputation between the social targets’ vertical spatial position and the amount of help that the social targets obtain from others. Study 3 cross-validated this mediating process by a measurement-of-mediation design. Those three studies help us comprehend how helping behavior occurs from the characteristics of help recipients as well as extend the influence of vertical spatial metaphor of morality from cognitive connection to action-relevant outcomes.